Simulation the Probability of Liberalizing Chlorin Gas from Urban Water Chlorination System in Alborz: With the Cancer Approach - Moradi, Reza; Nikpey, Ahmad; Saeidabadi, Hamzeh; Yari, Saeed (Asian Pacific Journal of Environment and Cancer, 2019)
Background: Qazvin province has suffered a lot of natural disasters (earthquakes) for a long time. so, the establishment of the first industrial city in Iran, has always been a source of concern. One of these problems is the possibility of chlorine gas leaking from the chlorination system of drinking water and treatment plant the existing ones are on the health of the inhabitants of this region. Material and method: This analytical study was carried out in Novorossiysk district of Alborz in December 2012. Initially, chlorine gas leakage scenarios from these facilities were simulated by ALOHA and WISER software, and then using the Emergency Level System, according to the CCPS Consultative Center’s Chemical Process Safety Advice, the Emergency Response Program was presented. Results: ALOHA software, in comparison with WISER software, has more precision to identify and address the consequences of chlorine gas leakage hazards and according to the simulation of this software in the event of a leak from the well and water resources unit at 8240 m from the area and at night 7520 meters will be affected. Due to the speed of delivering results through the WISER software, this software can be used at times when the operating speed is considered (incident time). Conclusion: According to the CCPS model, the emergency conditions were classified at levels 3 and 4, therefore, the relevant crisis management agencies (Qazvin Crisis Management Committee, Alborz City Health Center, Red Crescent and Firefighting Authority) should provide training maneuvers At Alborz city level, and informing people of cities and industrial companies, many efforts have been made to reduce human and environmental damage in case of possible leakage.